Change in composition and potential functional genes of microbial communities on carbonatite rinds with different weathering times - Chen, Jin; Li, Fangbing; Zhao, Xiangwei; Wang, Yang; Zhang, Limin; Yan, Lingbin; Yu, Lifei (Frontiers in Microbiology, 2022)
Organisms and time are important factors for rock weathering to form soils. However, weathering time is usually difficult to quantitatively study, and the potential microorganisms involved in rock weathering are difficult to identify qualitatively. Currently, there is no clear conclusion on how ecological strategies of carbonatite weathering rind microorganisms change with weathering time, and how the microbial composition and functional genes involved in element cycling change over two century-scale weathering time. In this study, we selected abandoned carbonate tombstones as the subject and used the date when the tombstones were erected by humans as the onset of weathering. Using metagenome sequencing methods, we investigated the trends in the composition of fungal, bacterial and archaeal communities of carbonate weathering rind and related elemental cycle functional genes during a weathering time of 19 to 213 years. The results showed that: (1) with the increase in weathering time, at the phylum level, microbial taxa gradually shifted from r-strategists (faster turnover rates, higher mortality rates, higher reproduction, lower competition rate) to K-strategists (slower turnover rates, lower mortality rates, lower reproduction, higher competition rate), which correspondingly increased the abundance of functional genes related to C and N cycles. (2) The properties of the parent rock layer determines the colonization and distribution of weathering rind microorganisms (especially prokaryotic microorganisms) and the corresponding functional gene abundance. Our study provides new insights into the weathering process of carbonate rocks.